The relationship between the pre‐admission CHA2DS2‐VASc score and proximal artery occlusion in patients with acute stroke and atrial fibrillation. (9th April 2015) - Sakamoto, Y.; Sato, S.; Hama, Y.; Nagatsuka, K.; Minematsu, K.; Toyoda, K.
<x xml:space="preserve">Abstract</x> Background and purpose The CHA2DS2‐VASc score is associated with severity and outcome of ischaemic stroke in patients with atrial fibrillation (AF). It was hypothesized that a high CHA2DS2‐VASc score was related to severity and outcome because of its association with proximal artery occlusion (PAO). This study aimed to elucidate the relationship between the CHA2DS2‐VASc score and PAO and to determine whether the effect of the CHA2DS2‐VASc score on severity or outcome is independent of PAO. Methods Acute stroke patients with AF were retrospectively enrolled. PAO was defined as occlusion at the internal carotid artery or proximal middle cerebral artery on admission magnetic resonance angiography. Multivariable analyses were performed to identify independent factors associated with PAO and determine the associations of the CHA2DS2‐VASc score with the initial National Institutes of Health Stroke Scale (NIHSS) score and poor functional outcome (discharge modified Rankin scale score 4–6). Results In all, 213 patients [102 women; median age 80 (interquartile range 71–86) years; NIHSS score 16 (9–22)] were enrolled. On multivariable analysis, the CHA2DS2‐VASc score (odds ratio 1.40, 95% confidence interval 1.12–1.76 per 1 point) was independently associated with PAO and correlated with the initial NIHSS score (standardized coefficient 0.198, P = 0.017). This association was not significant after further adjustment for PAO (0.080, P = 0.241). The CHA2DS2‐VASc score was independently related to poor outcome even adjusted for PAO (odds ratio 1.39, 95% confidence interval 1.03–1.88). Conclusion The CHA2DS2‐VASc score was associated with PAO in acute ischaemic stroke patients with AF. The CHA2DS2‐VASc score may be correlated with the NIHSS score through the presence of PAO and with poor functional outcome independently of PAO.